Pengaruh Investasi dan Indeks Pembangunan Manusia Terhadap Pertumbuhan Ekonomi di Kalimantan Utara - Darmawanto, Agus Tri; Mursalin, Reza Syahrullah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
The aim of this research is to determine the effect of investment and the human development index on economic growth in North Kalimantan Province. The data used panel data from 2019 to 2024 with five districts/ cities in North Kalimantan Province. Data obtained from the investment data processing information system for North Kalimantan Province and Central Statistical Agency for the Regency/City of North Kalimantan Province and North Kalimantan Province. Data analysis using panel data regression. The research results show that investment and the human development index partially have positive and significant effect on economic growth in North Kalimantan. Investment and the human development index simultaneously have a significant effect on economic growth in North Kalimantan.